Computer Aided Detection of Endobronchial Valves using Volumetric CT - Ochs, Robert A. (2009)
RATIONALE AND OBJECTIVES: The ability to automatically detect and monitor implanted devices may serve an important role in patient care by aiding the evaluation of device and treatment efficacy. The purpose of this research was to develop a system for the automated detection of one-way endobronchial valves that were implanted for less-invasive lung volume reduction. MATERIALS AND METHODS: Volumetric thin-section CT data was obtained for 194 subjects; 95 subjects implanted with 246 devices were used for system development and 99 subjects implanted with 354 devices were reserved for testing. The detection process consisted of pre-processing, pattern-recognition based detection, and a final device selection. Following the pre-processing, a set of classifiers were trained using AdaBoost to discriminate true devices from false positives. The classifiers in the cascade used two simple features (either the mean or maximum attenuation) of a local region computed at multiple fixed landmarks relative to a template model of the valve. RESULTS: FROC analysis was performed for the evaluation; the system could be set so the mean sensitivity was 96.5% with a mean of 0.18 false positives per subject. If knowledge of the number of implanted devices were incorporated, the sensitivity would be 96.9% with a mean of 0.061 false positives per subject; this corresponds to a total of 12 false negatives and 6 false positives for the 99 subjects in the test dataset. CONCLUSION: Software was developed for automated detection of endobronchial valves on volumetric CT. The proposed device modeling and detection techniques may be applicable to other devices as well as useful for evaluation of treatment response.